PENGELOLAAN SISTEM TRANSPORTASI OLEH DINAS PERHUBUNGAN KOTA PEKANBARU TAHUN 2013-2015 - Nia Gusti Lestari; Hasanuddin " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
This research is based on the Regulations of the regional city of Pekanbaru number 02 of 2009 about Traffic And Road Transport that the Department of transportation the city of Pekanbaru has the authority as a service to manage transportation in General. Problems occurred at the existing highway transportation in the city of Pekanbaru in between Oplet, City Bus and Metro Trans because of the low level of mobility and accessibility in transportation such as the operating system, the frequency of arrival on the uncertain transportation, the operation of urban transport is still the old already as Oplet and City Bus, and not of route diversion transport routes new oplet intersecting route Trans Metro Pekanbaru.A common purpose is to research described by the management of transportation department of transportation Pekanbaru. This is cityhe methodology, qualitative study data collection techniques used is, documentation, interviews and observation. While data analysis was descriptive.This study looked at the management of municipal Pekanbaru on mobility and accessibility on transportation and setting route study conducted transportation department on Oplet, City Bus and Trans Metro Pekanbaru.The result of this research suggests transportation system management done transportation department on the implementation of the route diversion on oplet and city bus with not been undertaken effectively and efficiently, as evidenced by at present well intersecting with the route Trans Metro Pekanbaru.While in the development of Trans Metro corridor can be done effectively and efficient, evidenced by 2 corridor and in 2015 to 8 corridor.Keywords: The Management Of Transportation System, City Transpor